Human Health Risk Assessment of Total and Organic Mercury in Fish and Seafood from Jakarta Bay, Indonesia - Susi Sulistia; Takeharu Goshima; Margaret Boohene; Fuzi Suciati Sastraatmaja; Muhammad Ihsan Sofyan; Esti Mega Maulidayanti; Agus Sudaryanto; Endro Soeyanto; Tia Agustiani; Rendi Handika; Jun Kobayashi; Yasumi Anan; et al. (Environments, 2026)
Mercury (Hg) contamination in seafood is a major environmental and public health concern because organic Hg, predominantly methylmercury (MeHg), bioaccumulates and biomagnifies through aquatic food webs. However, information on Hg speciation in fish and seafood from Indonesia remains limited. This study quantified total Hg (THg) and organic Hg (OHg) in 111 specimens representing 15 commercially important fish and seafood species collected from Jakarta Bay, Indonesia, and assessed the associated human health risk. Median THg concentrations ranged from 0.032 to 3.82 mg/kg dry weight (dw), whereas median OHg concentrations ranged from 0.014 to 2.95 mg/kg dw. A comparison with international and Indonesian food safety guidelines showed that Moses perch (Lutjanus russellii) exceeded the maximum permissible Hg concentration, whereas all other species complied with established limits. Median organic Hg accounted for 26.5–89.4% of THg. THg and OHg concentrations were significantly positively correlated with fish length but not weight. Most species presented negligible non-carcinogenic risks (hazard quotient, HQ < 1); however, 16% and 4% of evaluated exposures exceeded the HQ threshold for children and adults, respectively. Overall, Hg speciation combined with human health risk assessment provides a comprehensive evaluation of seafood safety beyond THg alone. These findings provide baseline data supporting consumption advisories, long-term Hg monitoring, and evidence-based risk management in Indonesia.